Analysis of inbreeding on parameters reproductive in a dairy herd at central cost - Calderón Velásquez, Jorge P. (2020)
With the objective was analyzing consanguinity on reproductive parameters in a dairy herd Was analyzed records from 4 044 cows Holstein’s breed, totalized 9 355 reproduction records, of a herd of dairy cattle on central coast, to evaluate the main effect of the inbreeding on traits reproduction as: age of pregnancy in heifers and age of first calving, calving interval and length of gestation. The 93,17% of the cows were inbred and the range were from 0,1283% to 31,4722% of inbred, the average inbreeding coefficient of all cows was 5,18%. Effect of inbreeding were estimated by a model that included fixed effects: year-seasons, sire groups, number of calving, age at calving, inbreeding. The inbreeding was included in the model as a classification (six class: 0; 3,125; 6,25; 9,375; 12,50 and >12,50%). The average of the age at pregnancy in heifers was 16,40 months and the age at first calving was 25,43 months, were not affected by the levels of inbreeding, show similar averages between the inbred and non-inbred groups, The direct effect of inbreed was estimated, the regression was -0,13128 ± 0,0241 months age at conception in heifers and -0,15263 ± 0,02381 months for age at calving respectively (P <0,01). The effect on calving interval and length of gestation was not significant the inbred, but the regression coefficients of the calving interval and length gestation were: 0,10934 ± 0,02746 months and -0,09986 ± 0,02594 days respectively (P><0,01).